Two new cephalochromin derivative from the Alternaria sp. ZG22. Issue 20 (23rd September 2021) - Song, Xin-Ming; Zhou, Xue-Ming; Li, Ya-Ling; Huang, Li-Bing; Chen, Cai-Cui; Gao, Yan; He, Lin; Mao, Xiao-qun; Chen, Bing; Liu, Jing-Wen; Liu, Hui-Jie; Song, Xiao-Ping; et al.
Abstract: Two new cephalochromin derivatives, prenylcephalochromin A (1 ), prenylcephalochromin B (2 ), along with cephalochromin (3 ) were isolated from the Alternaria sp. ZG22 obtained from a Dasymaschalon rostratum collected from the Hainan. The structures of two new compounds were elucidated by comprehensive spectroscopic methods. Compounds 1 -3 showed α -glucosidase inhibitory activity. Abstract : UF0001